The Expression of Two Splice Variants of the Kv3.1 Potassium Channel Gene Is Regulated by Different Signaling Pathways - Liu, Si-qiong J. (J Neurosci, 1998)
The Kv3.1 potassium channel gene gives rise to two different channel proteins, Kv3.1a and Kv3.1b, by alternative splicing of nuclear RNA. During development the levels of Kv3.1b mRNA (but not Kv3.1a) substantially increase in rat cerebellum after postnatal day 8. The molecular mechanism underlying the differential regulation of the two transcripts is not known. Using in vitro slices of cerebellum, we have found that basic fibroblast growth factor (bFGF) upregulates both Kv3.1a and Kv3.1b at this developmental stage, but that depolarization by elevated potassium concentrations is without effect. Combined treatment with bFGF and depolarization, however, prevents the increase in Kv3.1a transcripts and selectively increases Kv3.1b mRNA levels. A protein kinase C (PKC) inhibitor blocks the increase in Kv3.1a mRNA levels induced by bFGF alone but does not affect the increase in Kv3.1b mRNA. Measurement of nuclear protein kinase C activity shows that bFGF activates this enzyme and that depolarization blocks this activation. In contrast to these findings at postnatal day 8, bFGF fails to alter Kv3.1 transcripts in slices from adult animals, and PKC activity is enhanced rather than suppressed by depolarization. Our results indicate that different signaling pathways regulate Kv3.1a and Kv3.1b expression and suggest that Kv3.1a mRNA levels may be modulated by neuronal activity.